2009
DOI: 10.1007/978-1-60327-114-1_28
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Conservation and Cryopreservation of Ornamental Plants

Abstract: Today, the conservation of ornamental germplasm can take advantage of innovative techniques which allow preservation in vitro (slow growth storage) or in liquid nitrogen (cryopreservation) of plant material. Slow growth storage refers to the techniques enabling the in vitro conservation of shoot cultures in aseptic conditions by reducing markedly the frequency of periodic subculturing, without affecting the viability and regrowth of shoot cultures. Cryopreservation refers to the storage of explants from tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The improvement of storage techniques is necessary for successful bud regrowth and synthetic seed conversion, including of elite clonal germplasm, endangered cultivars [39,40], and storage of cultivar or species in commercial laboratories. Recently, slow growth storage has found applications in in vitro conservation of several ornamental species [41].…”
Section: Medium-term In Vitro Conservationmentioning
confidence: 99%
“…The improvement of storage techniques is necessary for successful bud regrowth and synthetic seed conversion, including of elite clonal germplasm, endangered cultivars [39,40], and storage of cultivar or species in commercial laboratories. Recently, slow growth storage has found applications in in vitro conservation of several ornamental species [41].…”
Section: Medium-term In Vitro Conservationmentioning
confidence: 99%
“…Besides their role in the ecological importance, these climbers are also very important in ornamental and medical uses. Ozudogru et al ( 2010 ) reported a review on slow-growth conservation and cryopreservation of ornamental species which refers to the in vitro conservation of shoot cultures by minimising their periodic subcultures without affecting the viability and revival of shoot cultures. Cryopreservation refers to the storage of explants at ultralow temperature of −196 °C, at which all biological activities within the cells are hampered.…”
Section: Introductionmentioning
confidence: 99%
“…Sorbitol at 0.1 M concentration was found to be effective in decreasing growth in Teucrium polium L. and Acheillea frarantissima respectively as reported by Rabba'a et al (2012) and Younis (2012). The use of low temperature from 4 to 18 °C and nutrient medium supplementation osmo-regulators with sucrose have been used to conserve explants for clonal propagation such as tubers, roots and ornamental species (Ozudogru et al, 2010). The low temperature increases the transfer interval to new medium and often regardless of the type and concentration of carbohydrate used (Lima-Brito et al, 2011).…”
Section: Introductionmentioning
confidence: 99%